Prevention of Bunched Basal Plane Dislocation Arrays in 4H-SiC PVT-Growth - Steiner, Johannes; Nguyen, B. D.; Sandfeld, S.; Wellmann, Peter (Trans Tech Publications Ltd, 2023)
To prevent arrays of basal plane dislocations (BPD) forming during grown 4H-SiC single crystals, the growth cell in physical vapor transport (PVT) growth was modified by adapting the temperature gradients, the seed attachment method and the seeding phase. The resulting reduction in stress was modeled numerically and the crystals were investigated by X-ray topography (XRT) and molten potassium hydroxide (KOH) etching. Due to these modifications, the formation of BPD arrays was completely suppressed.
CRIS-Team Scopus Importer:2023-06-23
Keywords: basal plane dislocations; numerical modeling; physical vapor transport; stress; X-ray topography